Prevalence of hypertension among rural population of Doiwala block, Dehradun, Uttarakhand India - Pooja, Pooja; Mittal, Yashoda (Recent Research in Science and Technology, 2013)
Hypertension is a major health problem in developed as well as in developing countries. The prevalence pattern of hypertension in developing countries is different from that in the developed countries. The increasing epidemic of hypertension in India was documented by studies done at various places across the country. Various studies estimated a prevalence rate of hypertension among urban population ranging from 1.24% in 1949 to 36.4% in 2003 and for rural people from 1.99% in 1958 to 21.2 % in 1994. Uttarakhand is a newly formed and one of the hilly states of the India with more than 70% rural population. Since very scanty reports are available on prevalence of hypertension from Uttarakhand so this community based cross sectional study was conducted to know about the prevalence of hypertension in rural population of an area of Uttarakhand. Gumaniwala, a village near Rishikesh was the place of survey. A total of 340 peoples aged 30 years and above were selected through simple random sampling method for the study. All the subjects underwent an interview through a pretested questionnaire and clinical examination. Blood pressure of all the study subjects was measured using standardized technique. All the data were analyzed using SPSS software version 16.0. The prevalence of hypertension was presented as percentage. The association between categorical variables and hypertension were tested using Chi square test. A p value of < 0.05 was considered statistically significant. The overall prevalence of hypertension and pre-hypertension was 33.2% and 40.6% respectively. The prevalence of hypertension among females is higher (34.2%) than in males (32.4%). Among all studied variables age, smoking and Body mass index (BMI) were significantly related with hypertension (p<0.05). Since prevalence of hypertension is associated with socio-demographic factors hence the identification of the variables influencing hypertension is an important aspect for taking appropriate preventive measures to stop increase in the incidence of hypertension.